1976
DOI: 10.1136/hrt.38.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Change in symptoms of hypertensive patients after referral to hospital clinic.

Abstract: and the Grove Health Centre, London At theirfirst visit to a hospital clinic 178 patients referred with a diagnosis of hypertension were given a self-administered questionnaire. They received a similar questionnaire 12 months later. Of the 178 patients 99 were not initially on treatment. Similarly 78 normotensive subiects were drawn randomly from the local population and sent a second questionnaire 10 months later. The symptoms at the first visit of the normotensive controls, the untreated hypertensive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
1
4

Year Published

1977
1977
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(100 citation statements)
references
References 6 publications
7
88
1
4
Order By: Relevance
“…Despite of being usually accepted as a potential cause of headache, 13 the association between severe hypertension and headache was predominantly described in previous studies, not controlling for confounding and for the awareness of hypertension. [22][23][24][25] It has been suggested that the awareness of the diagnosis may be a reason for the higher frequency of headache among patients with hypertension. 7,8 Since almost all participants of our study knew that they had hypertension, this potential bias on the association between the diagnosis of hypertension and the complaint of headache was naturally controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of being usually accepted as a potential cause of headache, 13 the association between severe hypertension and headache was predominantly described in previous studies, not controlling for confounding and for the awareness of hypertension. [22][23][24][25] It has been suggested that the awareness of the diagnosis may be a reason for the higher frequency of headache among patients with hypertension. 7,8 Since almost all participants of our study knew that they had hypertension, this potential bias on the association between the diagnosis of hypertension and the complaint of headache was naturally controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In this connection, the cofactorial role of endothelial dysfunction and decreased nitric oxide synthesis has been evaluated 9 and of considerable clinical relevance is the erectile dysfunction reported in untreated hypertensive men. 10,11 In such a situation, the problem gets further compounded by a prescribed antihypertensive, if impotence is one of its known adverse effects. 12 While there is no denying the risk of isolated erectile dysfunction in untreated cases, 4 it is often not recognised whether the impairment in controlled hypertension is due to the in¯uence of disease, drugs or both.…”
Section: Introductionmentioning
confidence: 99%
“…Since T2DM is independently related with nocturia, other factors apart from glucose metabolism must be present to cause this effect. Indeed, it was previously demonstrated that systemic diseases, such as hypertension, has been shown to be another factor related with nocturia both in normal [7][8][9][10] and in patients with T2DM. [12][13][14] However, in all these studies, peripheral BP measurements were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Although not all 5,6 but some studies have also shown that elevated blood pressure (BP) was another factor related with nocturia. [7][8][9][10] In patients with type 2 diabetes mellitus (T2DM), nocturia may be observed. Indeed not in all, 11 but some studies have shown that T2DM is associated with nocturia.…”
Section: Introductionmentioning
confidence: 99%